Pengaruh POE (Predict, Observe, Explain) terhadap Kemampuan Kolaborasi Siswa - Nirwana Anas; Ridho Rizky; Indah Adhani; Putri Chairany Hsb; Nofia Handayani (Tarbiatuna: Journal of Islamic Education Studies, 2023)
The purpose of this study was to determine the effect of applying the Predict Observe Explain (POE) learning model on the collaborative abilities of fourth grade students at SD Negeri 060858 Medan Tembung in the 2022/2023 academic year. The research methodology is quasi-experimental. The population of this study were all students of class IV-A and IV-B of SD Negeri 060858 which were the control class and the experimental class. The experimental class in this study was Class IV-A which was treated with the application of the Predict Observe Explain (POE) learning model, while the control class in this study was Class IV-B which was treated with the use of a traditional learning model (directed learning). .Based on the research findings, it can be concluded that the POE learning paradigm that encourages students to participate more actively has an effect on increasing students' capacity to collaborate. Keywords: Predict Observe Explain (POE) Learning Model, Collaboration Ability.